Reducing sugar intake in South Africa: a multilevel policy analysis of how global and regional diet policy recommendations find expression at country level - Mccreedy, Nicole (Department of Public Health and Family Medicine, 2022)
High intake of sugar has been recognised as a contributing factor to diet-related overweight and obesity, and as a determinant for non-communicable disease (NCD) emergence in LMICs. In 2015, the World Health Organization (WHO) released a guideline giving specific advice on limiting sugar intake in adults and children. Policy guidance has also been provided to promote healthy diets and/or restrict unhealthy eating habits at country-level. The study explored the extent to which global policy recommendations and directives on reducing sugar intake to prevent and control NCDs have found expression in policies issued at the Africa region, South African national or sub-national Western Cape provincial level. A systematic policy document review was conducted to identify policies between 2000 and 2020, at different levels of government using search terms related to sugar, sugar sweetened beverages (SSBs) and NCDs. NVivo 12 software was used to code and thematically analyse the data. A policy transfer conceptual framework was applied for the policy analysis to assess what ideas were transferred, including why and to what extent transfer occurred. Forty-eight policy documents were included in this review. Most were global or national level policies. It was evident that several global policy ideas on unhealthy diets and reduction of sugar intake had found expression in South African health policies, as well in the education and finance sectors. Global recommendations for effectively tackling unhealthy diets and NCDs are to implement a mix of cost-effective policy options employing a multisectoral approach. Local policy action has followed the explicit guidance from international agencies, and ideas on reducing sugar intake have found expression in sectors outside of health, to a limited extent. Together with the adoption of the sugar-sweetened beverages (SSBs) health tax, South Africa's experience offers learnings for other LMICs.